Sedentary behaviour and social anxiety in obese individuals: the mediating role of body esteem - Abdollahi, Abbas; Abu Talib, Mansor (Taylor & Francis, 2015)
Given that the prevalence of social anxiety in obese individuals is high, it is necessary that we increase our knowledge about the related factors that cause social anxiety in obese individuals. The present study sought to examine the role of body esteem as a mediator between sedentary behaviour and social anxiety. The participants were 207 overweight and obese individuals who completed the self-report measures. The structural equation modelling displayed that obese individuals with sedentary behaviour and poor body esteem were more likely to show social anxiety. Body esteem partially mediated between sedentary behaviour and social anxiety. Our results highlight the role of sedentary behaviour and body esteem as promising avenues for reducing social anxiety in obese individuals.